قرآن کریم میں مذکور اسماءالنبیﷺکی تفہیم اور مطالعہ سیرت میں ان کی اہمیت: Understanding the Names of the Prophet ﷺ mentioned in the Holy Quran and their importance in the study of Sirah - Hussain , Muhammad Muzamil; Waraich , Dr. Shams ul Arfin (Al-Amīr Research Journal for Islamic Studies, 2022)
In the Qur'an, Allah mentioned His Beloved ﷺ in addition to his personal names, but also with different attribute names which, apart from his greatness and dignity, highlight different aspects of the life of the Prophet ﷺ. Along with increasing the love of the Prophetﷺ, these names cover various aspects of the Prophet's life, from which many jurisprudential issues can be derived in addition to his dawah life, private and political affairs. Therefore, your names are scattered in the Holy Quran like pearls, which the people of love wrap around their necks and live in the love of the Prophet ﷺ. In the article under review titled "Understanding the Names of the Prophet ﷺ in the Holy Quran and their Importance in Studying the Sirah" the personal and attribute names of the Holy Prophet ﷺ will be explained in the light of different interpretations and hadiths which will not only make it possible to understand the blessed name but will also shed light on various aspects of Seerat Tayyaba. Key words: Names of the Prophet ﷺ, Prophet's biography, personal names, attribute names, study of the Qur'an.